Sperm-dependent asexual hybrids determine competition among sexual species - Janko, Karel; Eisner, Jan; Mikulíček, Peter (Scientific reports, 2019)
Interspecific competition is a fundamental process affecting community structure and evolution of interacting species. Besides direct competition, this process is also mediated by shared enemies, which can change the outcome of competition dramatically. However, previous studies investigating interactions between competing species and their parasites (parasite-mediated competition) completely overlooked the effect of 'sperm' parasites (i.e. sperm-dependent parthenogens or pseudogams) on competition. These organisms originate by interspecific hybridization, produce clonal gametes, but exploit parental species for their own reproduction, being therefore analogous to classical parasites. Here we use the reaction-diffusion model and show that pseudogams alter the outcome of interspecific competition significantly. They may either slow down competitive exclusion of the inferior competitor or even turn the outcome of competition between the species. Asexual organisms may thus have unexpectedly strong impact on community structure, and have more significant evolutionary potential than was previously thought.
Keywords: Sexual Behavior; Models, Biological; Host-Parasite Interactions; Female; Competitive Behavior; biologická evoluce; interakce hostitele a parazita; Spermatozoa; kompetitivní chování; mužské pohlaví; sexuální chování; spermie; Reproduction; biologické modely; zvířata; ženské pohlaví; Animals; Biological Evolution; Male; rozmnožování